The effect of L-arginine and its antagonist L-NAME and Methylene blue on sensory and cognitive function in mice: Farid J. Al-Tahan , Muhannad A. A. Al-Bayati and Salma J. Askar - Al-Tahan, Farid J. (The Iraqi Journal of Veterinary Medicine, 2012)
The present study was done to focus light on possible enhancement of the functional performance of male mice and female in neuronal behaviors by using L-arginine as a precursor of nitric oxide (NO). The results showed increase of latency period to reach the novel object in L-arginine treated groups and decrease in both L-NAME and methylene blue treated groups in both periods of treatment (15 and 30) days and were more prominent in male than in female mice as compared with control groups. Similar results were observed in passive avoidance latency period to enter the dark compartment. There was a reduction in latency period to reach the alternative arm of T-maze test in L-arginine treated groups and increase in both L-NAME and methylene blue treated groups in both periods of treatment (15 and 30) days in both genders. It could be concluded that L-arginine-NO pathway plays an important role in improving memory in male more than female mice.